2021
DOI: 10.15252/embj.2021108028
|View full text |Cite
|
Sign up to set email alerts
|

CARS senses cysteine deprivation to activate AMPK for cell survival

Abstract: Adenosine 5'‐monophosphate (AMP)‐activated protein kinase (AMPK) is an important cellular metabolite‐sensing enzyme that can directly sense changes not only in ATP but also in metabolites associated with carbohydrates and fatty acids. However, less is known about whether and how AMPK senses variations in cellular amino acids. Here, we show that cysteine deficiency significantly triggers calcium/calmodulin‐dependent protein kinase kinase 2 (CaMKK2)‐mediated activation of AMPK. In addition, we found that CaMKK2 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 52 publications
1
11
0
Order By: Relevance
“…In addition to its role in protein synthesis, the sulfur‐containing amino acid cysteine is critical in many biological processes including synthesis of coenzyme A, iron–sulfur (Fe‐S) cluster biogenesis and redox balance (Combs & DeNicola, 2019). In the current study, Yuan et al (2021) demonstrate that cysteine deprivation promotes a rapid and marked activation of AMPK. AMPK is a heterotrimeric protein complex composed of a catalytic α‐subunit and two regulatory subunits, β and γ.…”
Section: Figure Amp‐activated Protein Kinase (Ampk) Senses Low Amino ...supporting
confidence: 58%
See 2 more Smart Citations
“…In addition to its role in protein synthesis, the sulfur‐containing amino acid cysteine is critical in many biological processes including synthesis of coenzyme A, iron–sulfur (Fe‐S) cluster biogenesis and redox balance (Combs & DeNicola, 2019). In the current study, Yuan et al (2021) demonstrate that cysteine deprivation promotes a rapid and marked activation of AMPK. AMPK is a heterotrimeric protein complex composed of a catalytic α‐subunit and two regulatory subunits, β and γ.…”
Section: Figure Amp‐activated Protein Kinase (Ampk) Senses Low Amino ...supporting
confidence: 58%
“…In addition to its role in protein synthesis, the sulfur-containing amino acid cysteine is critical in many biological processes including synthesis of coenzyme A, iron-sulfur (Fe-S) cluster biogenesis and redox balance (Combs & DeNicola, 2019). In the current study, Yuan et al (2021) demonstrate that cysteine deprivation promotes a rapid and marked activation of AMPK. AMPK is a heterotrimeric protein complex composed of a catalytic a-subunit and two regulatory subunits, b and c. In mammals, there are two isoforms of a, two of b and three of c. AMPK activation is induced upon phosphorylation of residue Thr172 in the AMPK a-subunit (by liver kinase B1, LKB1; calcium/calmodulindependent protein kinase kinase 2, CaMKK2; or transforming growth factor-b-activated kinase 1, TAK1).…”
mentioning
confidence: 58%
See 1 more Smart Citation
“…The sample was prepared according to a preparation kit (Thermo: 90057), and LC-MS and data analysis were performed following the procedure described previously ( 23 , 24 ). A Q-Exactive Plus mass spectrometer (Thermo) coupled to an EASY-nLC 1200 HPLC system (Thermo) with an anoelectrospray ion source and operated in data-dependent mode was used to analyze the samples.…”
Section: Methodsmentioning
confidence: 99%
“…Recent investigations have shown that cysteine depletion activates AMPK through calcium/calmodulin-dependent protein kinase kinase 2 (CaMKK2). Interestingly, the cysteinyl-tRNA synthetase (CARS), which plays a canonical role in protein translation, recognizes lack of cysteines and activates AMPK via the cysteine–CARS–CaMKK2–AMPKg2 system, adapting cell survival to nutrient deprivation [ 282 ]. Mitochondrial CARSs in human cells are involved in endogenous cysteine hydropersulfide (CysSSH) synthesis in vivo and even catalyze co-translational cysteine polysulfidation, which are implicated in the modulation of mitochondrial biogenesis and bioenergetics, playing a central role in redox signaling, cellular translation, and energy metabolism [ 283 ].…”
Section: Amyotrophic Lateral Sclerosismentioning
confidence: 99%